2000
DOI: 10.1007/s004180000148
|View full text |Cite
|
Sign up to set email alerts
|

The apical membrane of intestinal brush cells possesses a specialised, but species-specific, composition of glycoconjugates – on-section and in vivo lectin labelling in rats, guinea-pigs and mice

Abstract: Brush cells are specialised epithelial cells that are assumed to represent chemoreceptors of the digestive tract. They comprise a small population of the epithelial cells lining the intestine, possess a unique ultrastructure and, in many aspects, resemble the receptor cells of taste buds. To characterise glycoconjugates possibly involved in a sensory function, we investigated brush cells in the small intestine of three species using lectin histochemistry in confocal light and thin-section electron microscopy. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 35 publications
1
13
0
Order By: Relevance
“…Phenol-water extraction, originally used to extract lipopolysaccharides, has been applied for the preparation of mucins (Gold et al, 1981), and glycocalyces (Caulfield et al, 1987). The glycocalyx of intestinal brush cells is a carbohydrate-rich material with a polyanionic nature that is composed of glycoconjugates that differ in glycosylation patterns in all species examined (Gebet et al, 2000). At present there is no comprehensive analysis of the protein components of the intestinal epithelial glycocalyx.…”
Section: Discussionmentioning
confidence: 99%
“…Phenol-water extraction, originally used to extract lipopolysaccharides, has been applied for the preparation of mucins (Gold et al, 1981), and glycocalyces (Caulfield et al, 1987). The glycocalyx of intestinal brush cells is a carbohydrate-rich material with a polyanionic nature that is composed of glycoconjugates that differ in glycosylation patterns in all species examined (Gebet et al, 2000). At present there is no comprehensive analysis of the protein components of the intestinal epithelial glycocalyx.…”
Section: Discussionmentioning
confidence: 99%
“…1987; Sato & Miyoshi, 1997). Gebert et al. (2000) reported that some BCs examined by electron microscopy showed an inhomogeneous distribution of lectin‐bound glycoconjugates.…”
Section: Discussionmentioning
confidence: 99%
“…The enterocyte brush border glycocalyx was more evident in B. capriscus than in S. pachygaster . This glycocalyx is known to mediate many functions such as the absorption of nutrients, microbial adhesion, antigen uptake and chemoreception and its alteration under pathologic conditions has been studied previously (Gebert et al ., ; Kavanaugh et al ., ; Løkka & Koppang, ). The meaning of such a developed glycocalyx is not clear (even with a lower number of residuals than other species, as noted previously), although it probably implies a greater need to regulate these processes in B. capriscus .…”
Section: Discussionmentioning
confidence: 99%